Fever and rash in an 11-month-old girl - Jamani, Nurjasmine Aida; Jahn Kassim, Puteri Shanaz (Academy of Family Physicians of Malaysia, 2016)
An 11-month-old girl presented with a 3-day history of high fever, irritability and decreased appetite. However, there was no coryza, cough, diarhoea or fits. On the third day, a generalised erythematous rash appeared after the fever subsided abruptly. The rash was pinkish in colour, non-pruritic and discrete, which initially started on the trunk and later spread to the face, neck and extremities within 2 days. On further questioning, she was found to be appropriately immunised for her age according to the Ministry of Health’s immunisation schedule. No similar illnesses existed in her family and the nursery she attended. On examination, the infant appeared well, with a normal body temperature of 37°C and stable vital signs. A generalised erythematous maculopapular rash was observed extending from the head to her legs, which blanched with pressure. Involvement of the buccal mucosa was absent, with no palpable lymph nodes. She was prescribed paracetamol syrup regularly and care givers advised to maintain her hydration. The child remained well and active throughout the course of the illness. The rash subsequently subsided within a couple of days.